Determinação de pesticidas no Rio Piquiri por LC/MS/MS - Moura, Eliel Rogério Rolim de (2013)
Water quality and conservation of aquatic environments assumed a leading condition for sustainability, not only related to the supply, but also the preservation of these ecosystems. The use of water, especially for supply to urban centers and irrigation in agriculture has favored upon the decrease of the reserves of clean water and therefore less dilution of pollutants, including pesticides. Pesticides are among the group of pollutants that can generate significant impacts on environments in which they are entered, some of which impacts are not yet fully known. Due to the growing demand for food and the consequent need to achieve greater productivity, pesticide use has increased significantly favoring the increase f these impacts. This agricultural production system is prevalent in the world and results in the presence of such pollutants in various aquatic environments, especially the surface regions, near of crop areas. In this context, monitoring of these pollutants in the field indicates its fate in the environment near its application showing more accurately its behavior in field, and provides reference information for program monitoring and evaluation of pesticides in these environments. This study examined samples of water and sediment Piquiri River, located in a region of high production of wheat, soybeans and corn in the state of Paraná, Brazil. This river is under direct influence of the application of pesticides of the region. Water samples were extracted with a mixture of dichloromethane:hexane and sediment samples with acetone:hexane and was concentrated 500 times for water and 25 times for sediment. The extracts were analyzed by LC / MS / MS and confirmed the presence of herbicides and fungicides used in the study region according to official data of the marketing period of the collections. The most impressive results in the water samples were the herbicide Atrazine, 0,030 μg L-1 and the fungicide Carbendazim, 0,178 μg L-1. In the sediment, the highest values were found for the fungicide Carbendazim, 26.8 μg L-1 and Azoxystrobin, 0.712 μg L-1, both in the third collection at the collection point 3.